2019
DOI: 10.1074/jbc.ra118.005477
|View full text |Cite
|
Sign up to set email alerts
|

An immune-stimulating proteoglycan from the medicinal mushroom Huaier up-regulates NF-κB and MAPK signaling via Toll-like receptor 4

Abstract: Edited by Xiao-Fan WangTrametes robiniophila Murr. (Huaier) is a mushroom with a long history of use as a medicinal ingredient in China and exhibits good clinical efficacy in cancer management. However, the antitumor components of Huaier and the underlying molecular mechanisms remain poorly understood. Here, we isolated a proteoglycan with a molecular mass of ϳ5.59 ؋ 10 4 Da from Huaier aqueous extract. We named this proteoglycan TPG-1, and using FTIR and additional biochemical analyses, we determined that its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…that has been approved by the Chinese Food and Drug Administration for cololitis (Chen, Wu, et al, 2018a; Sun et al, 2017). The main active ingredient of huaier is polysaccharide, which is a binding protein composed of 18 monosaccharides combined with 18 kinds of amino acids (Luo et al, 2016; Yang, Fan, et al, 2019a). Increasing evidence confirmed that huaier could induce the differentiation and apoptosis of cancer cells, improve the killing ability of immune cells, reverse tumor‐associated drug resistance, and inhibit the migration and invasion of tumor cells, and so on (Bao et al, 2016; Li et al, 2015; Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…that has been approved by the Chinese Food and Drug Administration for cololitis (Chen, Wu, et al, 2018a; Sun et al, 2017). The main active ingredient of huaier is polysaccharide, which is a binding protein composed of 18 monosaccharides combined with 18 kinds of amino acids (Luo et al, 2016; Yang, Fan, et al, 2019a). Increasing evidence confirmed that huaier could induce the differentiation and apoptosis of cancer cells, improve the killing ability of immune cells, reverse tumor‐associated drug resistance, and inhibit the migration and invasion of tumor cells, and so on (Bao et al, 2016; Li et al, 2015; Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…T reg cells specifically require c‐Rel to inhibit anti‐tumor effector responses. Yang et al revealed that Toll‐like receptor 4 (TLR4), which plays a vital role in innate immune response and cytokine production, closely participates in NF‐κB‐mediated immune regulation 62 . In our study, we found that icariin could significantly ameliorate the tumor immunosuppressive microenvironment by downregulating expression levels of PD‐L1, enhancing the proportion of infiltrating CD4 + /CD8 + T cells and reducing the abundance of MDSCs in tumors.…”
Section: Discussionmentioning
confidence: 48%
“…Polysaccharide was identified as a possible key ingredient in Huaier (24). Previous studies showed that Huaier exerted therapeutic effects on psoriasis (5), inflammation (6), and tuberous sclerosis (7). In dextran sulfate sodium-induced experimental colitis, Huaier suppressed the secretion of interleukin 1β (IL-1β) and the activation of caspase-1 via inhibiting NLRP3 inflammasome (8).…”
Section: Introductionmentioning
confidence: 99%